Inventarisasi Pohon Plus dalam Blok Koleksi di Taman Hutan Raya Wan Abdul Rachman - Moses Hasibuan; Indriyanto Indriyanto; Melya Riniarti (Department of Forestry, Faculty of Agriculture, University of Lampung, 2013)
Plus tree inventory was an activity for collecting and compiling data. Collection block was an area within Great Forest Park region that contains different types of plant, either endemic or non-endemic plants, which serves for protection and preservation, research, science, education, support the cultivation, culture, tourism and recreation. The information about the existence of plus trees on the collection block still rare. So, plus tree inventory still necessary to fulfill the data. This research was held in Wan Abdul Rachman Great Forest Park Collection Block at February to March 2012. The aim of this research is to identify the trees which has plus tree criteria. Data collected by using line terraced layers method which placed systematically. The collected data include the types of trees, trunk diameter, branch height, trunk straightness, tree's health condition, fruit production, branch corner, sphericity form of circumference stem, and the location of the plus tree. Based on the results, there were 9 species of trees that identified as plus trees, 7 species of wooden trees, which are 3 taboo trees (Tetrameles nudiflora), 1 dadap tree (Erythrina fusca), 1 purple coral tree (Pterospermum javanicum), 1 sandpaper tree (Ficus ampelas), 6 kapok trees (Ceiba pentandra), 1 red cedar tree (Toona sureni), 1 mindi tree (Melia azedarach) and 2 species of MPTS trees, 1 durian tree (Durio zibethinus), and 1 mango tree (Mangifera indica). Total number of individual tree that meets the plus tree criterias are 16 trees. Keywords: inventory, plus trees